Duch Święty w Programie nauczania religii - Słotwińska, Helena (Studia Pastoralne, 2008)
The article focuses on the programme for high schools. It consists of four parts. In the first part it draws attention to the existing relation between the knowledge of truths about the Holy Spirit and respect for the sacrament of Confirmation. In the second part – the presence of truths about the Holy Spirit are portrayed. The third part contains discussion of the truths present in the Programme. The theme of the fourth part is the next three truths that should be known by the students who are receiving the sacrament of Confirmation.